Preprint for the humanities – fiction or a real possibility? - Steven Laporte (Studia Historiae Scientiarum, 2017)
Even though the use of open preprint databases for scholarly publications is commonplace in several disciplines, their possibilities remain largely unexplored in the humanities. This article examines the emergence and the dynamics of academic preprint and evaluates the possibilities for introducing preprint for the humanities.